CHALLENGES FACED BY NURSES IN THE PROVISION OF MENTAL HEALTH SERVICES IN MASAKA REGIONAL REFERRAL HOSPITAL, MASAKA CITY. A CROSS-SECTIONAL STUDY. - Nanyonjo , Florence; Kimera , Donatus (Student's Journal of Health Research Africa, 2023)
Background: The purpose of the study is to assess the challenges faced by nurses in the provision of mental health in Masaka Regional Referral Hospital, Masaka City. Methodology: A descriptive cross-sectional study design that utilized quantitative methods of data collection was conducted at Masaka Regional Referral Hospital, for 3 days, 30 nurses were selected using the purposive sampling method. A structured questionnaire consisting of both open and closed-ended was used to collect data. The data collected was analyzed using Microsoft Excel, 2013, and arranged in fom1of tables, pie-charts, and graphs. Results: The majority 16(53%) of the respondents agreed that it is hard to develop a health worker-patient relationship with mentally ill patients due to the aggressive behavior of patients. The majority 22(73%) of the respondents said that the patient's economic status affected their services. The majority 16(53%) of the respondents said that drug stockouts affected the wellness pattern of mentally ill patients. The majority 17(57%) said they were affected psychologically while taking care of mentally ill patients. The majority 23(77%) mentioned that they had never been aggressively harassed by mentally ill patients. majority 18(60%) said that the facility administration rarely held training for the management of mental illnesses. Conclusion: Patient-induced challenges faced by nurses in the provision of mental health services included; difficulty in developing a nurse-patient relationship due to aggressive behaviour. Health facility-related challenges in the provision of mental health services included; drug stock-outs which affected the wellness pattern of patients and lack of training on the management of mental illnesses. Recommendation: The Ministry of Health and the Management of Masaka Regional Referral Hospital should encourage nurses to practice self-care and prioritize their well-being, resources and workshops on stress management techniques, and provide enough drugs to use during the provision of mental health services.